Correction of malnutrition in patients with oropharyngeal squamous cell carcinoma - A. M. Mudunov; D. B. Udintsov (Опухоли головы и шеи, 2015)
To treat oropharyngeal squamous cell carcinoma is a complex and multicomponent process. In so doing, most patients starting treatment have already manifestations of malnutrition resulting from underlying disease progression. The degree of malnutrition is determined by the site and sizes of a primary focus and generally remains permanent in patients with oropharyngeal squamous cell carcinoma at all treatment steps. Adequate nutritional support makes it possible to reduce the incidence of complications after surgical treatment and development of radiation responses, to enhance tolerability of treatment, and to improve quality of life in patients.